Use of the Scottish and Newcastle Anti-Emetic Pretreatment (SNAP) scheme in recovery from massive overdose of acetaminophen poisoning with acute liver failure - Case report - Torres-Maure, Moisés (2023)
Acetaminophen is a drug widely used in the world and easily accessible due to its antipyretic, analgesics characteristics, among others (1); however, exposure to toxic doses causes organic damage and even death. We present the case of an 18-year-old female patient who ingested 40 grams of acetaminophen and developed severe liver dysfunction, being treated with N-acetylcysteine (NAC) antidotal therapy according to the simplified scheme: Scottish and Newcastle Anti-emetic Pretreatment Paracetamol Poisoning Study Regimen (SNAP), presenting improvement in the clinical course and decrease in liver profiles, coagulation disorder, INR and resolution of the condition.